Environmental Performance dan Pengungkapan CSR terhadap Finacial Performance Perusahaan Manufaktur di BEI - Damayanti, Fera; Ardhi, Qisthi; Kurniawan, Rudy; Fabiola, Rivanka Wana (Jurusan Akuntansi Politeknik Negeri Pontianak, 2023)
Companies that have high profits are companies that have good financial performance. In order to get maximum profit, many companies still ignore the environmental and social impacts of the process of their activities. This research was conducted to determine and analyze the effect of environmental performance and CSR disclosure on the performance of financial manufacturing companies listed on the IDX. This study uses a quantitative approach and the type of data used is secondary data. The population used in this study included manufacturing companies listed on the IDX from 2016 to 2020, then selected using a purposive sampling technique so that a total sample of 27 companies that met the criteria was obtained. The data in this study were analyzed using multiple linear regression and using the SPSS 25 program. From the results of the data analysis that has been carried out, it shows that environmental performance has a negative effect and does not have a significant effect on financial performance. Disclosure of CSR has a negative and insignificant effect on financial performance. Environmental performance and CSR disclosure have no simultaneous effect on financial performance.